MINAT DAN HASIL BELAJAR SISWA SELAMA PEMBELAJARAN DARING - Siska Ananda Siska; Sabaruddin; Nina Rahayu (Jurnal Anifa: Studi Gender dan Anak, 2021)
The distribution of covid-19 causes the closure of institutions so that the learning activities are carried out at home with the online learning system. The roles of teachers and parents during online study are essential to foster student learning interests so that students can have a maximum yield.The study aims to know the impact online learning will have on the interest and study of student programs. The study involves qualitative methods. It uses qualitative methods. Research samples are listed as teachers, the parents and the students of the MIS Paya Bujok Tunong. Data collection techniques using an angket, interviews and documentaries. The data collection tools used are the interview sheets for teachers, parents and students, and interest study sheet Student. Studies indicate that online learning systems are causing students' interest in learning to be low. This is demonstrated by the spread of the angket that the interest of students learning about online learning is dominated by a low study interest criteria ata percentage of 37.5% or 6 of the 16 students and the results are then strengthened from resultsor This Interviews with students, teachers and student parents. And online learning causes students' learning results to decrease compared with the students' learning results when a face-to-face learning system. This is demonstrated by comparison of the results of students' learning by the value report card in which the student's acuity level at online learning is only 62.5 % far from the student's minimum percentage at face to face learning that's an 81.3% advance